On decentralized adaptive full-order sliding mode control of multiple UAVs - Xiang, Xianbo; Liu, Chao; Su, Housheng; Zhang, Qin (ISA transactions, 2017)
In this study, a novel decentralized adaptive full-order sliding mode control framework is proposed for the robust synchronized formation motion of multiple unmanned aerial vehicles (UAVs) subject to system uncertainty. First, a full-order sliding mode surface in a decentralized manner is designed to incorporate both the individual position tracking error and the synchronized formation error while the UAV group is engaged in building a certain desired geometric pattern in three dimensional space. Second, a decentralized virtual plant controller is constructed which allows the embedded low-pass filter to attain the chattering free property of the sliding mode controller. In addition, robust adaptive technique is integrated in the decentralized chattering free sliding control design in order to handle unknown bounded uncertainties, without requirements for assuming a priori knowledge of bounds on the system uncertainties as stated in conventional chattering free control methods. Subsequently, system robustness as well as stability of the decentralized full-order sliding mode control of multiple UAVs is synthesized. Numerical simulation results illustrate the effectiveness of the proposed control framework to achieve robust 3D formation flight of the multi-UAV system. •A new type of full-order sliding mode surface incorporating both the individual position tracking error and the synchronized formation error is designed in a de-centralized manner, through a more general information exchange topology rather than the specific ring-like communication topology proposed in the existed references.•A decentralized virtual plant controller is constructed which allows the embedded low-pass filter to attain the chattering free property of the networked sliding mode controller for synchronized formation flight of multi-UAV system.•Robust adaptive technique is integrated in the decentralized chattering free control design to handle unknown bounded uncertainties, by relaxing the restricted requirements for assuming a priori knowledge of bounds on the system uncertainty as stated in conventional chattering free control systems.•System robustness as well as stability of the decentralized adaptive full-order sliding mode control of multiple UAVs is established to achieve synchronized 3D formation flight under system uncertainty, by resorting to the graph theory and Lyapunov analysis.